Essentials for a successful registry: valid data, the right questions and timely execution. (1st October 2018) - Garcia‐Doval, I.; Stern, R.S.
Abstract: Linked Articles: Gerbens et al. Br J Dermatol 2018; doi: 10.1111/bjd.16714. Garcia‐Doval et al. Br J Dermatol 2018; 179 :863–871 . Grinich et al. Br J Dermatol 2018; 179 :540–541 .